The impact of phonetics and phonology on the Xitsonga orthography - Maluleke, Rivalani (My University, 2013)
The aim of this dissertation is to examine the impact of phonetics and phonology on the Xitsonga orthography. It looks at the history of Xitsonga orthography and the developments from the missionaries’ era in the 1800s until 2013. The study also examines the contribution made by the Tsonga Language Board, the Tsonga Language Committee and Pan South African Language Board (PanSALB) in the development of Xitsonga orthography. In addition, the study focuses on the Xitsonga speech sound types and the way they are spelled by the speakers. On the other hand, there are speakers who adhere to the standard orthography whereas on the other hand there are speakers who prefer to use speech sounds according to their respective dialects. The challenges which Xitsonga speakers face on a daily basis have been outlined and what can be done to resolve them. It is suggested that more Xitsonga dictionaries should be written and published and PanSALB should ensure that booklets that deal with Xitsonga spelling rules must be distributed as widely as possible
Thesis (M.A. ( Translation and Linguistics)) -- University of Limpopo, 2013
Keywords: Phonetics; Phonology; Xitsonga orthography; Tsonga Language Board; Tsonga language -- Orthography and spelling.; Phonetics; Phonology; Grammar, Comparative and general -- Phonology